COGNITIVE GRAMMAR ON “SMASH”: PERSPECTIVES FROM LANGACKER’S FRAMEWORK - Chong Seng Tong; Ng Yu Jin; Noor Azam Abdul Rahman; Zalina MohdKasim (Indonesian JELT, 2013)
The language system allows us to express perceived events indifferent ways using different linguistic resources. Ability toperform this task goes beyond the notion of prescriptivegrammar, which makes no connection between language and thecognitive mind. Cognitive grammar focuses on the way weconstruct our ideas. Meaning is equated with conceptualization.Semantic structures are characterized Based on the ideas andtheses posited by Langacker with regards to Cognitive Grammar,we seek to illustrate how our cognitive minds help us manipulatethe use of language, especially the grammatical items.Keywords: Cognitive Grammar, Langacker, Pedagogy, Smash